1996
DOI: 10.1021/jp960155m
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Electron-Transfer Dynamics at a Sensitizing Dye−Semiconductor (TiO2) Interface

Abstract: The charge injection dynamics of dye sensitization from a surface-bound dye (coumarin 343 (C343)) to the conduction band (CB) of the TiO2 is reported here for the first time. Ultrafast fluorescence dynamics demonstrate that the charge injection from the C343 dye to the CB of the TiO2 occurs on a time scale of ca. 200 fs. The charge injection efficiency is attributed to strong electronic coupling between the dye and TiO2 energy levels. The results yield a rate of injection of 5 × 1012 s-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
374
4
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 419 publications
(390 citation statements)
references
References 12 publications
11
374
4
1
Order By: Relevance
“…Our conclusion that electron injection occurs on a picosecond and subpicosecond time scales is consistent with conclusion of Willig and coworkers that electron injection in Ru(dcbpy) 2 (H 2 O) 2 2+ -sensitized nanocrystalline TiO 2 films occurs in <7 ps. Similar subpicosecond excited-state quenching has also been reported for adsorption of coumarin dye onto nanocrystalline TiO 2 films 27 and has been inferred from fluorescence quenching experiments for an oxazine dye into SnS 2 . 28 This result is however at variance the results of Kamat and co-workers, which indicate that electron injection from Ru(dcbpy)(bpy) 2 2+ into a range of different semiconductor films occurs in 2-10 ns.…”
Section: Discussionsupporting
confidence: 79%
“…Our conclusion that electron injection occurs on a picosecond and subpicosecond time scales is consistent with conclusion of Willig and coworkers that electron injection in Ru(dcbpy) 2 (H 2 O) 2 2+ -sensitized nanocrystalline TiO 2 films occurs in <7 ps. Similar subpicosecond excited-state quenching has also been reported for adsorption of coumarin dye onto nanocrystalline TiO 2 films 27 and has been inferred from fluorescence quenching experiments for an oxazine dye into SnS 2 . 28 This result is however at variance the results of Kamat and co-workers, which indicate that electron injection from Ru(dcbpy)(bpy) 2 2+ into a range of different semiconductor films occurs in 2-10 ns.…”
Section: Discussionsupporting
confidence: 79%
“…There is now a growing consensus that the electron injection process, in dye-sensitized nanocrystallineTiO 2 films, can proceed on subpicosecond time scales for a range of different sensitizer dyes. [4][5][6][7][8][9][10][11] We recently found that these injection kinetics are moreover rather insensitive to variations in experimental conditions (e.g., electrolyte composition and application of electrical bias 6,11 ). In contrast, the corresponding charge recombination reaction between injected electrons and dye cations has been reported to exhibit time constants ranging from picoseconds to milliseconds.…”
Section: Introductionmentioning
confidence: 99%
“…If this state lies energetically above the conduction band edge of the colloid, electron injection to the semiconductor can occur on a fast or ultrafast time scale. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The resulting charge-separated system was reported to undergo relaxation and recombination processes, with typical time constants in the range from 10 fs up to 500 µs, 9,12,21,24,25 dependent on the dye/semiconductor system. According to Marcus theory one of the main parameters for the electron injection rate is the difference in free energy ∆G between the donor and acceptor states.…”
Section: Introductionmentioning
confidence: 99%